A NOTE ON DIMENSION OF WEAK HYPERVECTOR SPACES - Taghavi, A.; Hosseinzadeh, R. (Italian Journal of Pure and Applied Mathematics, 2014)
In this paper, we study the dimension of weak hypervector spaces. First, we define linearly dependence and independence of vectors and also basis of weak hyper-vector spaces and then prove some results in this field. Finally, we consider weak subhypervector spaces of such spaces.